2010
DOI: 10.1016/j.ijid.2010.02.570
|View full text |Cite
|
Sign up to set email alerts
|

Medical needs assessment and infectious diseases concerns in rural Honduras - Implications for medical relief planning

Abstract: For the analysis regression models were done.Results: The HDI varied in the states from 0.710689-0.865577. ID mortality disparity ranges from rate of 1.55-49.62 deaths/100,000pop; IHD mortality from 14.77-97.78 deaths/100,000pop; and TA mortality from 12.63-47.05 deaths/100,000pop. Linear regression models evidenced that the relationship between epidemiological and social variables and HDI was negative for ID, positive for IHD and neutral for TA. Those states with higher HDI and its components had lower ID mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The short-term medical mission HOMBRE has been serving three communities in northern Honduras for five years. Needs assessments conducted in 2008 and 2009 described clinical needs of the populations [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-term medical mission HOMBRE has been serving three communities in northern Honduras for five years. Needs assessments conducted in 2008 and 2009 described clinical needs of the populations [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Needs assessment studies administered in 2008 and 2009 [ 13 ], as well as the Adult Health Initiative database [ 14 , 15 ] in Coyoles and La Hicaca, demonstrated differences in health status and burden of both chronic and infectious diseases between the communities of La Hicaca and Coyoles. Whitney et al reported a decreased odds ratio for obesity, diagnosis of gastroesophageal reflux disease, and receipt of analgesics, multivitamins, and proton pump inhibitors/H2 blockers in the population of La Hicaca, as compared to Coyoles [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group created the Adult Health Initiative (AHI) in 2009 to help optimize and standardize the care provided by the relief team, as well as to begin addressing chronic illness [ 2 , 3 ]. A novel clinical encounter form was developed that employed multiple algorithms, including screening for diabetes, assessing candidacy for antihelminthic therapy and prenatal vitamins, and chronic conditions such as gastrointestinal illnesses and musculoskeletal concerns.…”
Section: Introductionmentioning
confidence: 99%